The comparison of the players` participation in the effectiveness of the offence in basketball between European and NBA teams - Tsamourtzis, E.; Karpidis, A.; Mavridis, G.; Sfingos, N. (World Congress of Performance Analysis of Sport VIII, 2008)
Comparing European and NBA teams, we observe some differences in the offensive contribution of the players. Even though we avoided to statistically measure the two and three point field goals, due to the dissimilar distance of the 3 point field line, the tendency of NBA teams to make 2 point field goal attempts and European teams to make 3 point field goal attempts is obvious. The fewer turnovers of NBA players possibly imply an advanced readiness and individual skill, while the most committed fouls of European players are possibly a result of the strict FIBA regulations (5 fouls in Europe and 6 fouls in the NBA) and also of the "physical game" of NBA players. The larger offensive contribution from starters Point G ard and Shooting Guard as well as the smaller one from starters Small Forward, Power Forward and Center of European teams compared to the same NBA players, possibly indicates the tendency of peripherals in Europe for more final attempts at the moment that in the NBA, the game is played from the "tall" ones, inside the racquet. Before the present research, we were under the impression that nonstarter players contributed more in the NBA teams than in European ones. This impression is being reversed by the results which prove that nonstarters players of European teams had a larger participation in the effectiveness of the attack than the equivalent NBA players and specifically the nonstarters Power Forward and Center. This result probably indicates that the nonstarters "tall" players of European teams don`t differ from the starters as much as the corresponding NBA players.